Pengaruh Jenis Media Tanam terhadap Pertumbuhan Benih Cabai Rawit (Capsicum frutescens L.) - I PUTU OKA WIDIARTA; IDA AYU MAYUN; ANAK AGUNG MADE ASTININGSIH (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2021)
The Effect of Various Planting Media on The Growth of Rawit Chili (Capsicum frutescens L.) Research on the effect of the type of planting medium on the growth of cayenne pepper seeds has been carried out from the beginning of March to the end of April 2020 at the Kebun Bibit Taman Agro Inovasi BPTP Bali. This study used a completely randomized design (CRD) with three treatments and nine replications. The treatments tested were P0: fertile soil; P1: 50% fertile soil + 50% cow dung compost; and P2: 50% fertile soil + 50% chicken manure compost. The data obtained were analyzed by variance, followed by the 5% LSD test. The results showed that cayenne pepper with a mixed planting medium of fertile soil and cow dung compost gave the best results compared to other treatments for all research variables. At the age of 42 days after planting, the plant height reaches 10.40 cm; 9.85 cm; and 8.64 cm on planting media P1, P2, and P0, respectively. In accordance with the order of the three treatments, the average values ??of other parameters were respectively: the number of leaves 6.03, 5.80, and 5.52; rod diameter: 2.04 mm, 1.90 mm and 1.80 mm; root length: 14.52 cm, 13.86 cm, and 12.07 cm; total fresh weight: 1.730 g, 1.650, and 1.314 g; total plant oven dry weight: 0.174 g, 0.161 g, and 0.126 g; percentage of seed mortality: 7.72%, 8.33%, and 9.10%; and the percentage of seed growth: 92.28%, 91.67%, and 90.90%.